VD_FINDINFO Décision / 2015 / 402 vom 18. Mai 2015 - VD Tribunal cantonal (2015)
TORT MORAL, INDEMNITÉ POUR DÉTENTION, NON-LIEU, CLASSEMENT DE LA PROCÉDURE, FAUTE | 319 CPP (CH), 429 al. 1 let. b CPP (CH), 429 al. 1 let. c CPP (CH), 429 CPP (CH), 430 al. 1 let. a CPP (CH), 430 CPP (CH)